O direito material do trabalho e a reforma trabalhista: estudo analítico da Lei nº 13.467/17 – positivação de institutos já consagrados - Duarte, Vinicius Franco (2019)
This work is an analysis of the Law nº 13.467/17. This law, better known as labor reform, has modified several articles of the labor laws consolidation. The proposal of the present work is to promote a study of the reform itself, not of its object, but of what had been reformed. Initially, it is showed an analysis of Brazil´s historical moment when took place the first reformist movements and political agreements to approve the legal text. Next, it is discussed the significant change that ocurred by the Reform with the edition of the MP 808/17 and its ephemeral existence, with the legal consequences of its discreet and melancholy exit from the legal order. Further, it advances to the core of the subject matter of this study, through the analysis of the changes promoted in the CLT articles. At this point of the work, it is evidenced its greatest brand and ineditism, namely: the approach made to the articles that have changed has the unique purpose of delimiting the degree of innovation brought by the reform, its scope and depth, so as to allow us to ascertain whether it was a really innovative legal diploma and an instrument of deep changes in the legal-labor order or whether it is only the most of the same, that is, changes that have come to establish what has long been proposed and practiced by doctrine and jurisprudence. Thus, the work is directed to respond to its proposed central questioning. At the end, the conclusion will determine whether referential values for labor law and its relations, such as the dignity of the worker and the good faith, were, in fact, mitigated or despised by the reformist text or if the changes were only conceptual and, as such, unable to threaten the nuclear integrity of the Brazilian legal-labor system